Procedural efficiencies, lesion metrics, and 12-month clinical outcomes for Ablation Index-guided 50 W ablation for atrial fibrillation. Issue 6 (6th March 2021) - O'Brien, Jim; Obeidat, Mohammed; Kozhuharov, Nikola; Ding, Wern Yew; Tovmassian, Lilith; Bierme, Cedric; Chin, Shui Hao; Chu, Gavin S; Luther, Vishal; Snowdon, Richard L; Gupta, Dhiraj
Abstract: Aims: The safety of Ablation Index (AI)-guided 50 W ablation for atrial fibrillation (AF) remains uncertain, and mid-term clinical outcomes have not been described. The interplay between AI and its components at 50 W has not been reported. Methods and results: Eighty-eight consecutive AF patients (44% paroxysmal) underwent AI-guided 50 W ablation. Procedural and 12-month clinical outcomes were compared with 93 consecutive controls (65% paroxysmal) who underwent AI-guided ablation using 35–40 W. Posterior wall isolation (PWI) was performed in 44 (50%) and 23 (25%) patients in the 50 and 35–40 W groups, respectively, P < 0.001. The last 10 patients from each group underwent analysis of individual lesions ( n = 1230) to explore relationships between different powers and the AI components. Pulmonary vein isolation was successful in all patients. Posterior wall isolation was successful in 41/44 (93.2%) and 22/23 (95.7%) in the 50 and 35–40 W groups, respectively ( P = 0.685). Radiofrequency times (20 vs. 26 min, P < 0.001) and total procedure times (130 vs. 156 min, P = 0.002) were significantly lower in the 50 W group. No complication or steam pop was seen in either group. Twelve-month freedom from arrhythmia was similar (80.2% vs. 82.8%, P = 0.918). A higher proportion of lesions in the 50 W group were associated with impedance drop >7 Ω (54.6% vs. 45.5%, P < 0.001). Excessive ablation (AI >600 anteriorly, >500 posteriorly) was more frequent in the 50 W group (9.7% vs. 4.3%, P < 0.001). Conclusion: Ablation Index-guided 50 W AF ablation is as safe and effective as lower powers and results in reduced ablation and procedure times. Radiofrequency lesions are more likely to be therapeutic, but there is a higher risk of delivering excessive ablation.